Identification of an anti-lipopolysacchride factor possessing both antiviral and antibacterial activity from the red claw crayfish Cherax quadricarinatus. (October 2016) - Lin, Feng-yu; Gao, Yan; Wang, Hao; Zhang, Qiu-xia; Zeng, Chang-lin; Liu, Hai-peng
Abstract: It is well-known that anti-lipopolysacchride factors (ALFs) are involved in the recognition and elimination of invading pathogens. In this study, the full-length ALF cDNA sequence of the red claw crayfish Cherax quadricarinatus (termed CqALF ) was cloned from a suppression subtractive hybridization library constructed using red claw crayfish hematopoietic tissue cell (Hpt cell) cultures following challenge with white spot syndrome virus (WSSV). The full-length cDNA sequence of CqALF was 863 bp, and the open reading frame encoded 123 amino acids with a signal peptide in the N-terminus and a conserved LPS-binding domain. Unlike most ALFs, which are highly expressed in haemocytes, high expression levels of CqALF were detected in epithelium, the stomach and eyestalks, while lower expression was detected in Hpt, nerves, the heart, muscle tissue, gonads, haemocytes, intestines, gills and the hepatopancreas. To further explore the biological activities of CqALF, mature recombinant CqALF protein (rCqALF) was expressed and purified using a eukaryotic expression system, and an antimicrobial activity test was carried out. rCqALF clearly exerted antiviral activity, as evidenced by the severe disruption of the envelope of intact WSSV virions following co-incubation of virions with rCqALF. Additionally, pre-incubation of WSSV with rCqALF resulted in both a significant reduction in WSSV replication in red claw crayfish Hpt cell cultures and an increased survival rate among animals. Furthermore, rCqALF was effective against both Gram-negative bacteria and Gram-positive bacteria, particularly Shigella ﬂexneri and Staphylococcus aureus. A membrane integrity assay suggested that rCqALF was unlikely to disrupt bacterial membrane integrity compared to cecropin P1. Taken together, these data suggest that CqALF may play an important role in immune defence in the crustacean C. quadricarinatus. Highlights: rCqALF clearly exerted antiviral activity, as evidenced by the severe disruption of the envelope of intact WSSV virions. rCqALF resulted in both a significant reduction in WSSV replication and an increased animal survival rate. rCqALF was effective against both Gram-negative bacteria and Gram-positive bacteria.